Penerapan Metode Certainty Factor untuk Mendiagnosa pada Tanaman Kacang Tanah Berbasis Web (International Forum of Researchers and Lecturers, 2025)
Groundnut plants must be well maintained so that they can be food crops that have economic value and high fat and protein content. Many farmers still plant with the old pattern so that peanut plants are less fertile because they are affected by pests and other diseases. So with an expert system to diagnose peanut plants can help farmers or the general public in knowing the solution if experiencing problems or symptoms of this peanut plant. The application of the WP (weighted product) method can help the application become structured. From the results of the study, the expert system for diagnosing peanut plants can help many people for use as fundamental insights.